Biodegradation mechanism of phenanthrene by halophilic hortaea sp. B15 - Risky Ayu, Kristanti; Hadibarata, Tony; Al Farraj, Dunia A.; Elshikh, Mohamed Soliman; Alkufeidy, Roua M. (Springer International Publishing, 2018)
This aim of the study is to investigate a halophilic bacterium Hortaea sp. B15, isolated from petroleum-contaminated soil for biodegradation of phenanthrene. Hortaea sp. B15 has the ability to completely degrade phenanthrene (100 mg/L) under salinity 10% within 1-week incubation. The metabolitic product of phenanthrene was identified and assayed by using ultraviolet-visible spectrophotometer and mass spectral analysis. Result revealed that Hortaea sp. B15 metabolized phenanthrene to form 9,10-phenanthrene quinone, salicylic acid, and gentisic acid. Hortaea sp. B15 has an efficient utilization of phenanthrene in high-saline liquid medium. All the results indicated that the fungus has a promising application for the study of high-molecular-weight PAH biodegradation and contaminated saline-alkali soil bioremediation.